Undifferentiated carcinoma with osteoclast-like giant cells of the pancreas: a rare case report and review of the literature - Si, Lu; Liu, Yihan; Lin, Zhiyu; Qin, Qiuwen; Zhang, Yuxu; Deng, Demao; Lu, Zhao (Frontiers in Surgery, 2025)
BackgroundUndifferentiated carcinoma with osteoclast-like giant cells of the pancreas (UC-OGCP) is an exceedingly rare malignant tumour that accounts for less than 1% of all pancreatic nonendocrine neoplasms.Case presentationWe present a case of UC-OGCP in a 46-year-old male patient who was referred to our hospital after the incidental identification of a cystic tumour in the pancreas. Computed tomography (CT) revealed a 1.4 × 1.4 × 1.6-cm mass in the pancreatic head. Surgical resection was performed because it was difficult to determine the degree of malignancy of the tumour through clinical assessment. Intraoperative frozen-section pathology confirmed that the tumour was a malignant neoplasm. Pancreaticoduodenectomy was subsequently conducted. Histopathological studies confirmed the diagnosis of UC-OGCP.ConclusionThe clinical symptoms of UC-OGCP are nonspecific, and there are no distinct serological markers. Diagnosis relies primarily on endoscopic biopsy or postoperative pathology. We report this case of UC-OGCP and provide a literature review on the clinicopathological features, differential diagnosis, treatment, and prognosis of UC-OGCP, aiming to improve the understanding of this disease.